1999
DOI: 10.1046/j.1464-5491.1999.00003.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between blood glucose level and mortality in Type 2 diabetes mellitus: a systematic review

Abstract: Aim To review the relationship between blood glucose level and mortality in patients with Type 2 diabetes mellitus (DM) as reported in the literature. for papers were: Type 2 DM; follow-up for at least 3 years; glucose or glycated haemoglobin (HbA 1c ) was used as parameter; published in the form of an article. Additionally all references in the selected articles that dealt with the relationship between blood glucose level and mortality in Type 2 DM were included in the search.Results Twenty-seven eligible art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
2
6

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 96 publications
(123 reference statements)
2
45
2
6
Order By: Relevance
“…For the patients with Type II diabetes in our study, fasting plasma glucose was a predictor for all cardiovascular end-points, including stroke, and its association with CVD mortality was independent of all other variables (Model 3). A recent systematic review found that 23 out of 27 prospective studies in Type II diabetic patients showed a positive association between poor glycaemic control and either total or CVD mortality [54].…”
Section: Discussionmentioning
confidence: 99%
“…For the patients with Type II diabetes in our study, fasting plasma glucose was a predictor for all cardiovascular end-points, including stroke, and its association with CVD mortality was independent of all other variables (Model 3). A recent systematic review found that 23 out of 27 prospective studies in Type II diabetic patients showed a positive association between poor glycaemic control and either total or CVD mortality [54].…”
Section: Discussionmentioning
confidence: 99%
“…Despite these baseline similarities and equal likelihood of receiving treatment, African Americans and Hispanics had significantly worse control of hypertension and African Americans had worse control of diabetes. This poor control is especially worrisome in light of research that demonstrates that poor glucose control contributes to the risk of micro-and macrovascular complications and mortality (15)(16)(17)(18). Poorly controlled hypertension has been reported in one study to be the strongest predictor of the development of coronary heart disease in people with diabetes (19).…”
Section: Discussionmentioning
confidence: 99%
“…Table 6. Effect of Fenugreek on Hemoglobin (HbA1c) in type 2 diabetes In patients with type 2 diabetes previous studies have shown an association between the degree of hyperglycemia and increased risk of microvascular complications (Klein, 1995), sensory neuropathy (Alder et al 1997), myocardial infarction (Klein, 1995;UKPDS,1998), stroke (Lehto et al 1996), macrovascular mortality (Groeneveld et al 1999) and all cause mortality (Wei et al 1998;Knuiman et al 1992). Generally, these studies measured glycemia as being high or low or assessed glycemia on a single occasion, whereas repeated measurements of glycemia over several moths or year would be more informative.…”
Section: Resultsmentioning
confidence: 99%